1994
DOI: 10.1515/hfsg.1994.48.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscope Images of Black Spruce Wood Sections and Pulp Fibres

Abstract: The surfaces of pulp fibres and of microtomed sections of black spruce (Picea mariana) wood were examined with an atomic force microscope (AFM) under ambient conditions. The images of the section surfaces clearly show features of the underlying cell wall structure. An apparent lamellation, with periodicity of 30-200 nm is observed in cross-sections of the S2 layer. AFM images of unbeaten and beaten unbleached kraft pulp fibre surfaces indicate the orientation of the component microfibrils; flbrillar material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Some investigations used AFM for the characterisation of pulp fibres. [28,29] Even though some limitations of AFM are mentioned in these studies, the authors demonstrated the usefulness of this method.…”
mentioning
confidence: 89%
“…Some investigations used AFM for the characterisation of pulp fibres. [28,29] Even though some limitations of AFM are mentioned in these studies, the authors demonstrated the usefulness of this method.…”
mentioning
confidence: 89%
“…Gray et al used AFM to study the local surface variations in pulp, such as the orientation of microfibrils and the aspect of fibrillation by beating 18 -20 and such parameters as lamellation for wood. 19 Baker et al studied the surface topography of Valonia cellulose I microcrystals under propanol and water and obtained images that revealed clear structural details consistent with the 0.54-nm repeat unit (glucose) along the cellulose chains. An intermolecular spacing of about 0.6 nm was also described.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy AFM has become highly valued for evaluating wood, fiber, and paper surfaces (Hanley and Gray 1994;Bo¨ras and Gatenholm 1999;Hanley and Gray 1999;Wistara et al 1999;Niemi et al 2002).…”
Section: Resultsmentioning
confidence: 99%